2015
DOI: 10.1007/s00520-015-2634-8
|View full text |Cite
|
Sign up to set email alerts
|

Supportive care needs of Mexican adult cancer patients: validation of the Mexican version of the Short-Form Supportive Care Needs Questionnaire (SCNS-SFM)

Abstract: SCNS-SFM has acceptable psychometric properties and is suitable to evaluate supportive care needs of cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
2
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 21 publications
3
34
2
9
Order By: Relevance
“…The PDL domain of the SCNS-SF34 had a moderate correlation with the MSAS-PHYS and the SF-12 v2 Physical Component Summary scores. These findings were similar to those found in Chinese patients with colorectal cancer [11], Chinese patients with breast cancer [8], Mexican patients with cancer [10], etc. Similar to previous studies, we also observed moderate correlations between the PDL domain and other psychological outcomes, such as the HADS, the MSAS-PSYCH and the SF-12 v2 MCS, which implied that unmet physical and daily living needs would lead to psychological distress.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The PDL domain of the SCNS-SF34 had a moderate correlation with the MSAS-PHYS and the SF-12 v2 Physical Component Summary scores. These findings were similar to those found in Chinese patients with colorectal cancer [11], Chinese patients with breast cancer [8], Mexican patients with cancer [10], etc. Similar to previous studies, we also observed moderate correlations between the PDL domain and other psychological outcomes, such as the HADS, the MSAS-PSYCH and the SF-12 v2 MCS, which implied that unmet physical and daily living needs would lead to psychological distress.…”
Section: Discussionsupporting
confidence: 89%
“…There are 5 domains, including physical and daily living needs (PDL), psychological needs (PSY), patient care and support needs (PCS), health systems and information needs (HSI) and sexuality needs (SEX). The SCNS-SF34 has been validated in different cancer populations, such as China [8], France [9] and Mexico [10]. In Chinese populations, the construct validity and reliability have been established in women with breast cancer in Hong Kong [8] and patients with colorectal cancer in Hong Kong and Taiwan [11] only.…”
Section: Introductionmentioning
confidence: 99%
“…The minimum difference between two high weight values should be 0.10. If the difference is smaller than 0.10, the item is a cyclical one and should be removed (29).…”
Section: Resultsmentioning
confidence: 99%
“…The SCNS-SF34 has been rigorously tested for reliability and validity with Spanish cancer survivors. [18,19] Scores of the SCNS-SF34 can range between 0 and 136. [20,21] High scores mean higher level of unmet needs.…”
Section: Methodsmentioning
confidence: 99%